Identification of cardiotoxicity related to non-small cell lung cancer (NSCLC) treatments: A systematic review - Chan, Stefanie Ho Yi; Khatib, Yasmin; Webley, Sherael; Layton, Deborah; Salek, Sam (Frontiers in Pharmacology, 2023)
Introduction: In the last few decades, there has been a rapid development in cancer therapies and improved detection strategies, hence the death rates caused by cancer have decreased. However, it has been reported that cardiovascular disease has become the second leading cause of long-term morbidity and fatality among cancer survivors. Cardiotoxicity from anticancer drugs affects the heart’s function and structure and can occur during any stage of the cancer treatments, which leads to the development of cardiovascular disease. Objectives: To investigate the association between anticancer drugs for non-small cell lung cancer (NSCLC) and cardiotoxicity as to whether: different classes of anticancer drugs demonstrate different cardiotoxicity potentials; different dosage of the same drug in initial treatment affect the degree of cardiotoxicity; and accumulated dosage and/or duration of treatments affect the degree of cardiotoxicity. Methods: This systematic review included studies involving patients over 18 years old with NSCLC and excluded studies in which patients’ treatments involve radiotherapy only. Electronic databases and registers including Cochrane Library, National Cancer Institute (NCI) Database, PubMed, Scopus, Web of Science, ClinicalTrials.gov and the European Union Clinical Trials Register were systematically searched from the earliest available date up until November 2020. A full version protocol of this systematic review (CRD42020191760) had been published on PROSPERO. Results: A total of 1785 records were identified using specific search terms through the databases and registers; 74 eligible studies were included for data extraction. Based on data extracted from the included studies, anticancer drugs for NSCLC that are associated with cardiovascular events include bevacizumab, carboplatin, cisplatin, crizotinib, docetaxel, erlotinib, gemcitabine and paclitaxel. Hypertension was the most reported cardiotoxicity as 30 studies documented this cardiovascular adverse event. Other reported treatment-related cardiotoxicities include arrhythmias, atrial fibrillation, bradycardia, cardiac arrest, cardiac failure, coronary artery disease, heart failure, hypertension, ischemia, left ventricular dysfunction, myocardial infarction, palpitations, and tachycardia. Conclusion: The findings of this systematic review have provided a better understanding of the possible association between cardiotoxicities and anticancer drugs for NSCLC. Whilst variation is observed across different drug classes, the lack of information available on cardiac monitoring can result in underestimation of this association.